Control of the photoelectric generator for used in feeding of the independent wind turbine system - Mohammed Kendzi; Abdelghani Aissaoui; Mohamed Abid; Ahmed Tahour (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
In this paper, a hybrid power system is proposed to eliminate any interruption caused to absence of power supply network by the Fusion between the wind source and the photovoltaic source to create a hybrid system with internal power supply autonomy. The hybrid power system includes a solar and wind source whose wind energy conversion system is based on a doubly fed induction generator. The photovoltaic conversion system extracts the maximum power from the sun. A part of this power is used to supply the rotor of a doubly fed induction generator; the rest is injected in the grid. The connection between the two conversion systems is made by means of static converters (chopper/inverter). In the photovoltaic conversion chain, a controller for tracking the maximum power point is designed using the direct search approach the Perturb and observe method. The wind energy conversion system contains a doubly fed asynchronous generator with a control system of generated powers by the technique of the fuzzy logic. The simulation was done to prove the validity of the strategy and of the control method used for the control of the power generated by the hybrid system.